2018
DOI: 10.1039/c8dt02813c
|View full text |Cite
|
Sign up to set email alerts
|

Smoothing the single-crystal to single-crystal conversions of a two-dimensional metal–organic framework via the hetero-metal doping of the linear trimetallic secondary building unit

Abstract: The two-dimensional (2D) metal-organic framework (MOF) [Cd2.25Co0.75(BTB)2(DEF)4]·2(DEF)0.5 (1a, BTB = benzene-1,3,5-tribenzolate; DEF = N,N'-diethylformamide) featuring linear trimetallic cluster secondary building units (SBUs) and replaceable DEF solvates reacts smoothly with dipyridyl ligands DPS, DPDS, and BIPY (DPS = 4,4'-dipyridyl sulfide; DPDS = 4,4'-dipyridyl disulfide; BIPY = 4,4'-bipyridine), yielding three-dimensional (3D) non-interpenetrated [Cd2.25Co0.75(BTB)2(DPS)2]·xSol (2) and [Cd2.25Co0.75(BTB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…In these SBUs, each Eu 3+ or Tb 3+ ion was associated with two chelating carboxylates, a pair of chelating–bridging carboxylates in a complementary fashion, and two H 2 O solvates. It is also notable that this double-deckered structure resembles those found in {[Ln­(BTB)­(H 2 O) 2 ]·3DMF·2H 2 O} n (Ln = La, Nd, Sm, Er) and other 2D (6,3) networks sustained by linear trinuclear SBUs. Looking along the c direction, one can observe 1D channels with hexagonal apertures (Figure b).…”
mentioning
confidence: 63%
“…In these SBUs, each Eu 3+ or Tb 3+ ion was associated with two chelating carboxylates, a pair of chelating–bridging carboxylates in a complementary fashion, and two H 2 O solvates. It is also notable that this double-deckered structure resembles those found in {[Ln­(BTB)­(H 2 O) 2 ]·3DMF·2H 2 O} n (Ln = La, Nd, Sm, Er) and other 2D (6,3) networks sustained by linear trinuclear SBUs. Looking along the c direction, one can observe 1D channels with hexagonal apertures (Figure b).…”
mentioning
confidence: 63%
“…The motivation for introducing Ca 2+ into a Cd 2+ /H 3 BTB assembly originated from our quest to incorporate Ca 2+ into the linear Cd 3 -based two-dimensional (2D) MOF of [Cd 3 (BTB) 2 (DEF) 4 ]·2(DEF) 0.5 [ 62 , 63 ], as we and others have demonstrated that the heterometallic combinations of Cd/Zn, Cd/Co, and Zn/Co are readily tolerated in linear trimetallic cluster SBUs [ 26 , 66 ]. Our previous trial of the solvothermal reaction of Cd(NO 3 ) 2 ∙4H 2 O and H 3 BTB in a DEF/H 2 O/HNO 3 mixed solvent with CaSO 4 yielded a 3D anionic MOF of [Et 2 NH 2 ] 2 [Cd 5 (BTB) 4 (DEF) 2 ]∙4.75DEF featuring a zigzag-shaped Cd 5 cluster SBU [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…The motivation for introducing Ca 2+ into a Cd 2+ /H 3 BTB assembly originated from our quest to incorporate Ca 2+ into the linear Cd 3 -based two-dimensional (2D) MOF of [Cd 3 (BTB) 2 (DEF) 4 ]•2(DEF) 0.5 [62,63], as we and others have demonstrated that the heterometallic combinations of Cd/Zn, Cd/Co, and Zn/Co are readily tolerated in linear trimetallic cluster SBUs [26,66] [65]. The [Et 2 NH 2 ] + cations likely arose from the acid-catalyzed hydrolysis of DEF [67][68][69][70], and subsequently served as a template for the framework formation.…”
Section: Synthesis and Materials Characterization Of Mofmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this approach topologically identical, but functionally diverse MOFs can be obtained in the solid state. There is no topological change or structural transformation expected during this process. In this context, metal ions or metal clusters in the 2D MOFs can be exchanged in an SCSC manner. However, these metal ion exchange reactions are out of the scope of this review.…”
Section: Structural Transformationsmentioning
confidence: 99%